PERAN ZAKAT PRODUKTIF DENGAN PEMBERIAN MODAL USAHA DALAM MENINGKATKAN EKONOMI UMAT - Putra, Purnama; Hasbiyah, Wiwik (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
The purpose of this paper is to know the role of productive zakat with the provision of venture capital in improving the economy of the people. Through the descriptive-analysis of the literature conclusion of this paper that through the provision of vocational capital by using productive zakat funds will increase the productivity of society and will eventually increase the level of national production which is an indicator of macroeconomic growth. With the distribution of zakat to the underprivileged will be the equitable distribution of public income which will eventually increase the aggregate demand in the consumption of society in macroeconomic studies is a powerful tool in the growth and equity of economic development. Another benefit of zakat distribution productively will reduce the unemployment rate, as many people have the opportunity to strive with the bailout of zakat.